Relationship between skin-to-skin contact during the first hour of life and duration of exclusive breastfeeding - Alejandra Prian-Gaudiano; Daniela Horta-Carpinteyro; Andrea Sarmiento-Aguilar (Permanyer, 2024)
Background: Exclusive breastfeeding (BF) has the greatest potential impact on child mortality of any preventive intervention. Skin-to-skin contact (SSC) during the first hour of life is beneficial for initiating BF; however, routine separation of mother and infant is still common. This work aimed to demonstrate that SSC during the first hour of life is associated with a greater frequency and duration of exclusive BF. Methods: This is an observational case-control study. We reviewed the medical records of patients born between 2016 and 2022 classified as cases or controls based on the history of SSC in the first hour of life. Statistical analysis was performed using SPSS version 28. Results: We included 362 medical records, of which 200 (55.2%) had SSC and were considered cases; the 162 (44.8%) who did not have SSC were considered controls. Those who received SSC were more likely to receive exclusive BF at 3 (163 [81.5%] vs. 94 [58%], p < 0.001) and 6 months of age (147 [73.5%] vs. 83 [51.2%], p < 0.001). Conclusions: Patients who received SSC in the first hour of life were more likely to receive exclusive BF at 3 and 6 months of age. Promoting and respecting this practice is essential to increase the possibility of a newborn to be exclusively breastfed for the first 6 months of life.